Motherhood as a Source of Empowerment of Women in Yoruba Culture - Taiwo Makinde (Nordic Journal of African Studies, 2004)
The paper looks into Yoruba culture with emphasis on motherhood and how it empowers women in Yorubaland. It also looks at other areas of Yoruba perception of women and how these different perceptions empower women in Yoruba culture. It tries to find ways by which consideration of Yoruba culture as regards women can contribute to the improvement of life for women generally.